2015
DOI: 10.1177/0049475514566531
|View full text |Cite
|
Sign up to set email alerts
|

Consultation of traditional bone setters instead of doctors: Is it a sociocultural and educational or social insurance problem?

Abstract: Although improvements have occurred in the access to and utilisation of healthcare services, consultation by patients of bone setters seems to be a sociocultural and educational issue rather than a problem of lack of medical insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is most likely because of the failure of TBS treatment or complications. 15,16 Ideally, the school teachers should set an example for the students, parents, and society. However, in this study, we found a strong belief in the TBS practice, which might help increase the popularity of TBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely because of the failure of TBS treatment or complications. 15,16 Ideally, the school teachers should set an example for the students, parents, and society. However, in this study, we found a strong belief in the TBS practice, which might help increase the popularity of TBS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that patients' decision to attend TBS and not hospital is mainly due to the dependence on their sponsors for treatment in addition to cultural beliefs. 3,4 According to Omololu B et al Since several efforts in society as poverty or lack of education are not the major causes of seeking the help of the traditional healers, but probably the culture and traditional beliefs. 5 Serious TBS complications like limb gangrene are avoidable.…”
Section: Introductionmentioning
confidence: 99%
“…7,14,16 Studies in Turkey and India also indicated high rates of complications due to the activities of traditional bone setters. 22,37 The high rate of failure has been linked to the methods used by traditional bone setters which are not based on scientific knowledge and basic principles of infection prevention and control. 5,6,18,22,30 To this end, there have been calls to educate and train the traditional bone setters in effective management of open and closed fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many aspects relate to the health and disease process. There is a pragmatic identification and orientation about these aspects, since they guide the way society and management behave in the context of health, directly affecting those individuals most affected 36,37 .…”
Section: The Influence Of Sociocultural Aspects In the Construction Omentioning
confidence: 99%